Forestry component in the protection system against harmful phenomena in the Precarpathian region - Tkachuk, O. M.; Oliynyk, V. S. (Forestry and Forest Melioration, 2019)
Introduction Water-regulating and soil-protective capabilities are very important in the complex of environment-forming functions. This issue is particularly relevant for the Pre-Carpathian Upland with the area of 13 thousand km2, on which, after a long-term agricultural crop, the environmentally optimal ratio of land has been significantly disturbed, including excessive plowing of lands (> 45%) and anthropogenic activity decrease in forest cover (? 30%). Along with rainfall and gley and boggy soils spreading, it brings about the surface runoff and the development of intense erosion which covers 16% of the territory. The aim of the study was to assess the forest cover, its composition, age classes and forest types, as well as necessary forestry measures among protective measures against harmful natural phenomena. Materials and Methods Water catchments are the main objects of forest use in preventing negative natural phenomena. It is possible to organize an ecologically balanced intersectoral system within them for the sustainable use of land, forest, and water natural resources. The research was done in 18 small river basins where we studied the qualitative and quantitative characteristics of the forest cover, which are related to the land erosion prevention, a decrease in flood intensity and augmentation of groundwater resources, namely the forest cover of the catchments, the age and species structure of stands, and the division of forests into categories. The area of the river basins ranges from 100 to 910 km2, average altitudes range from 260–590 m above sea level and forest cover ranges from 10 to 59 %. Using the materials of the Ukrderzhlisproekt subcompartment database, as of 2010, we analyzed the forest fund and the distribution of forests by age, composition, and categories for two typical river basins of the Middle Carpathian region. Results Taking into consideration that the Carpathian region is densely populated and has an ancient agricultural tradition, we consider that a radical increase in the forest cover in its territory can worsen the socio-economic conditions there. Under these circumstances, there are two solutions to the problem: To form stable landscapes by afforestation of low-productive, erosion-hazardous and eroded lands, as well as slopes with a steepness of more than 15°; The increase in forest cover should not be confined to the entire territory as a whole, but to the catchments of the hydrographic network, which are closed geosystems with their own water regime characteristics and destructive processes. Conclusions The Carpathian forests perform important water-regulating, water conservation and soil protecting functions. However, due to the low forest cover in this territory, they can act as the only and main factor in optimizing the water regime and preventing soil erosion. We came to the conclusion that the main measures to enhance the protective functions of the Carpathian region forests should include two levels: a) catchments of rivers and streams with optimization of their forest cover, rational distribution of forests, creation of protective stands on agricultural lands; b) forest land with reproduction of indigenous stands, optimization of age groups of stands and forest categories, ecologic felling and usage of environmentally friendly technologies. 1 Fig., 2 Tables, 14 Refs.